Evaluation of PCR-Restriction Profile Analysis and IS2404 Restriction Fragment Length Polymorphism and Amplified Fragment Length Polymorphism Fingerprinting for Identification and Typing of Mycobacterium ulcerans and M. marinum - Chemlal, K. (American Society for Microbiology, 2001)
Mycobacterium ulcerans and M. marinum are emerging necrotizing mycobacterial pathogens that reside in common reservoirs of infection and exhibit striking pathophysiological similarities. Furthermore, the interspecific taxonomic relationship between the two species is not clear as a result of the very high phylogenetic relatedness (i.e., >99.8% 16S rRNA sequence similarity), in contrast to only 25 to 47% DNA relatedness. To help understand the genotypic affiliation between these two closely related species, we performed a comparative analysis including PCR restriction profile analysis (PRPA), IS2404 restriction fragment length polymorphism (RFLP), and amplified fragment length polymorphism (AFLP) on a set of M. ulcerans (n = 29) and M. marinum (n = 28) strains recovered from different geographic origins. PRPA was based on a triple restriction of the 3′ end region of 16S rRNA, which differentiated M. ulcerans into three types; however, the technique could not distinguish M. marinum from M. ulcerans isolates originating from South America and Southeast Asia. RFLP based on IS2404 produced six M. ulcerans types related to six geographic regions and did not produce any band with M. marinum, confirming the previous findings of Chemlal et al. (K. Chemlal, K. DeRidder, P. A. Fonteyne, W. M. Meyers, J. Swings, and F. Portaels, Am. J. Trop. Med. Hyg. 64:270–273, 2001). AFLP analysis resulted in profiles which grouped M. ulcerans and M. marinum into two separate clusters. The numerical analysis also revealed subgroups among the M. marinum and M. ulcerans isolates. In conclusion, PRPA appears to provide a rapid method for differentiating the African M. ulcerans type from other geographical types but is unsuitable for interspecific differentiation of M. marinum and M. ulcerans. In comparison, whole- genome techniques such as IS 2404-RFLP and AFLP appear to be far more useful in discriminating between M. marinum and M. ulcerans, and may thus be promising molecular tools for the differential diagnosis of infections caused by these two species.